2013
DOI: 10.1109/tvcg.2013.88
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Constrained-Environment Redirected Walking Instructions Using Search Techniques

Abstract: A goal of redirected walking (RDW) is to allow large virtual worlds to be explored within small tracking areas. Generalized steering algorithms, such as steer-to-center, simply move the user toward locations that are considered to be collision free in most cases. The algorithm developed here, FORCE, identifies collision-free paths by using a map of the tracking area's shape and obstacles, in addition to a multistep, probabilistic prediction of the user's virtual path through a known virtual environment. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(46 citation statements)
references
References 17 publications
1
43
0
Order By: Relevance
“…In this way, any number of conditions and repetitions can be done using the maximum available tracking space without redirection or interaction from the experimenter, while providing enough narrative to the user to behave naturally. As already discussed by Zmuda et al [31], we can expect different behavior from people in a narrow maze-like environment in comparison to wide, open spaces. Prediction is also potentially easier in the second case because the traveled path will diverge earlier compared to a narrow maze, since humans generally follow short and smooths trajectories to their target.…”
Section: Designmentioning
confidence: 57%
See 2 more Smart Citations
“…In this way, any number of conditions and repetitions can be done using the maximum available tracking space without redirection or interaction from the experimenter, while providing enough narrative to the user to behave naturally. As already discussed by Zmuda et al [31], we can expect different behavior from people in a narrow maze-like environment in comparison to wide, open spaces. Prediction is also potentially easier in the second case because the traveled path will diverge earlier compared to a narrow maze, since humans generally follow short and smooths trajectories to their target.…”
Section: Designmentioning
confidence: 57%
“…Both Zmuda et al [31] and Nescher et al [14] used graph representations of their respective virtual environments. This graph representations are predefined and consist of nodes and edges connecting two nodes.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitzsche et al [12] and Su et al [19] suggested an approach that dynamically minimizes the introduced curvature, but does not make imperceptibility a primary goal. A new way for planning RETs was proposed by Zmuda et al [25]. Their algorithm (FORCE) employs probabilistic planning and uses a terminal state evaluation function to determine feasible RETs that have to be used.…”
Section: Related Workmentioning
confidence: 99%
“…Following the idea of probabilistic planning of redirection [25], the paper introduces a planning framework that is based on a rigorous definition of redirection as an optimization problem. This allows applying optimization techniques from control theory.…”
Section: Introductionmentioning
confidence: 99%